Justice Perspective on Agrarian Reform in Realizing People’s Welfare - Prakoso, Bhim; Hariyani, Iswi; Ali, Moh. (Fakultas Hukum Universitas Airlangga, 2024)
This paper analyzes agrarian reform from the perspective of justice in realizing people’s welfare. The aim of agrarian reform is to organize land management, both in terms of asset management and access for the benefit of the people, so that an interesting legal issue to study in depth is equitable land management. It is necessary to understand that the no. of inequality in land control and ownership creates disparities which are correlated with imbalance. Agrarian reform based on asset management and access is expected to be able to answer the problem of inequality, especially in the object of agrarian reform. This research was conducted using a normative juridical method with a statutory approach and a conceptual approach. Agrarian reform can be interpreted as the government’s efforts to organize assets and community access related to land, which so far has been felt to have a lot of inequality in control and ownership. This arrangement is very important to provide certainty and access to manage assets so that they can provide equitable welfare. Fair land management is part of the state’s constitutional mandate regarding the utilization of agrarian resources for a country’s economy which is structured and aimed at the maximum prosperity of the people. As a benchmark for the success of implementing agrarian reform is the creation of legal certainty regarding land ownership as capital for the welfare of the people with justice.